COVID-19, FINANCIAL RISK AND THE AIRLINE INDUSTRY - Kasım Kiracı (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
The aim of this study is to investigate which financial variables increases or decreases the risk of the bankruptcy of airlines during periods of crisis when there is a possibility of financial distress. In this study, financial variables that affect financial distress in airlines and the possibility of bankruptcy were analyzed. In the framework of the study, the financial data from 35 airlines were examined. We employed the Altman (1968) Z-score, Springate (1978) S-score and Zmijewski (1984) J-score financial distress prediction models. The findings indicate that in times of crisis, when the probability of financial distress and bankruptcy increases (such as with Covid-19), leverage level, asset structure, firm size, firm profitability and liquidity ratio have a significant effect on an airline’s probability of bankruptcy score.